Analysis and implementation of volume flexibility in manufacturing plans - Oke, Adegoke (Cranfield University, 1999)
Manufacturing flexibility - the ability to change or respond quickly has been heralded as a major competitive weapon for manufacturing organisations operating in turbulent markets and markets characterised by fierce competition and rapid developments in technology. It is also important for the achievement of new management paradigms such as time-based competition, lean production, business process re-engineering and mass customisation. However, many issues on the concept of manufacturing flexibility such as, the clarification of why flexibility is needed, when it is needed, and how it can be implemented in manufacturing organisations have not been sufficiently addressed and resolved in the literature. This research project has been carried out to resolve some of these issues by focusing on one aspect of manufacturing flexibility - volume flexibility. The research design, which was developed to address the research issues, comprised the use of both quantitative and qualitative research methods. The quantitative research method is an exploratory mail survey of UK manufacturing plants in all the major industrial classifications. The survey was used to obtain broad patterns and evidence concerning the conditions that drive manufacturing plants to require volume flexibility and also to identify the mechanisms which manufacturing plants employ to achieve volume flexibility. The qualitative research method is an explanatory case-based research. Manufacturing plants in each sector that responded to the survey and provided rich and contrasting information about the issues being investigated were selected for the case study research. The case study research was used to confirm the survey results (triangulation) and more importantly to explain the trends and patterns observed in the survey analysis. The research concluded that high variability in demand levels is a major driver of volume flexibility and that it is generic in nature. Other drivers of volume flexibility were also identified. However, the applicability of these drivers to manufacturing plants was found to be independent of the sector to which the plants belong but on other specific characteristics of the plants. Mechanisms being employed to achieve volume flexibility in UK manufacturing plants were identified and referred to as enablers of volume flexibility. These enablers are not sector dependent but they do depend on specific market conditions, and their perceived costs and benefits. Substitute and complementary enablers were identified. Substitute enablers can be used to replace other enablers to achieve volume flexibility and complementary enablers aid other enablers in achieving volume flexibility. The research project also identified strategies, which can be employed by manufacturing plants to implement the enablers in achieving volume flexibility.